Pelatihan Pencarian Referensi Penelitian di Jurnal Bereputasi dan Penggunaan Reference Manager Mendeley Serta Spinner-id untuk Meningkatkan Publikasi Ilmiah di Kalangan Akademik Secara Online - Nugroho, Tatas Ridho; Kasnowo, Kasnowo; Verlandes , Yuliasnita (Fakultas Ekonomi Universitas Islam Majapahit, 2021)
This training is a community service activity that aims to increase knowledge and skills for academics, especially students at the Majapahit Islamic University and other universities in general. This activity was carried out online using the Zoom application for approximately 120 minutes, the material presented was looking for references in reputable journals and using the Mendeley application and spinner-id for faraphrasing in order to reduce the level of similiarity in the results of checking on turnitin. The results obtained after the implementation of this activity is an increase in the knowledge, insight and skills of the participants in writing scientific papers, both theses and articles to be published in journals. The participants were certainly very excited because they got additional knowledge about the complexities of publishing scientific journals which are now a reference for evaluating higher education performance from publications by lecturers and students by Ristekbrin.